Development of a Web-Based Food and Beverage Ordering System for University Canteens Using the Laravel Framework at University of Technology Yogyakarta - Ardani, Dheyvina; Aji, Adam Sekti (Kirana Publisher (KNPub), 2024)
The canteen at University of Technology Yogyakarta (UTY) often experiences overcrowding, particularly during peak hours, leading to long queues and potential errors in order processing. This research aims to design and develop a website-based food ordering system using the Laravel framework to facilitate the ordering process for students, lecturers, and staff, while also assisting canteen owners in efficiently managing orders. The system allows users to select menus, place orders, and complete payments online, significantly reducing the need for in-person queuing. The solution is expected to improve the canteen environment, providing a more organized and comfortable space for the UTY academic community. Functionality testing using Black Box Testing demonstrated that all core features operated as intended without issues. Additionally, usability testing through the System Usability Scale (SUS) yielded an average score of 97.58, categorizing the system in the